Eksplorasi Flora Potensial Sebagai Tanaman Hias Di Kawasan Wisata Air Terjun Talalang Jaya Desa Telentam Kabupaten Merangin - Pitri Handayani (Pendidikan Biologi STKIP YPM Bangko, 2019)
Research about exploration of potential flora as an ornamental plant in the Talalang Jaya Waterfall area is another aspect of forest product utilization. The forest plant has the potential as an ornamental plant is currently in great demand by the community. In addition to decorating homes or garden filler elements, ornamental plants have developed as export commodities. Exploration activities are proclaiming one of the first steps in the efforts of the conservative tumbling which began to be threatened by the great auction of building auctioneers and the development of industrial plants. This research is descriptive explorative with the roaming method represented randomly. Exploration of potential plants of seamless tanks in the area of Talalang Jaya Waterfall is obtained as many as 14 types, namely: Sonerila oblique, Sonerila pulchella, Begonia sp, Dracaena surculosa, Macodes petola, Agrostophyllum sp, Spathoglottis sp, Costus speciosa sp, Amomum apiculatum, Aglaonema, Alocasia sp, Scindapsus sp, Homalonema sp, dan Dendrobium.